2010
DOI: 10.1038/nchem.794
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of cortistatins A, J, K and L

Abstract: The cortistatins are a recently identified class of marine natural products characterized by an unusual steroidal skeleton and have been found to inhibit differentially the proliferation of various mammalian cells in culture by an unknown mechanism. We describe a comprehensive route for the synthesis of cortistatins from a common precursor, which in turn is assembled from two fragments of similar structural complexity. Cortistatins A and J, and for the first time, K and L, have been synthesized in parallel pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(36 citation statements)
references
References 55 publications
(76 reference statements)
0
36
0
Order By: Relevance
“…5 Below, we present a series of representative examples of applications of this strategy, together with a discussion of its use in practice.…”
Section: Introductionmentioning
confidence: 99%
“…5 Below, we present a series of representative examples of applications of this strategy, together with a discussion of its use in practice.…”
Section: Introductionmentioning
confidence: 99%
“…The selective index was 7-100-fold in comparison with those for several cancer cell lines. Subsequent chemical modification study revealed that desacyl mixture of senegasaponins (44) and tenuifolin (45) exhibited no anti-proliferative activity against either HUVECs or tumor cells, indicating that the 28-O-glycoside moiety and methoxycinnamoyl group were essential for HUVEC-selective growth inhibition. Senegin III (40) inhibited VEGF-induced in vitro tubular formation of HUVECs and bFGF-induced in vivo neovascularization in the mouse Matrigel plug assay.…”
Section: Senegasaponins From Senega Radixmentioning
confidence: 99%
“…[42][43][44][45][46][47][48][49][50] We also reported the synthetic study of 24, in which the 7-endo-selective intramolecular Heck reaction and oxy-Michael reaction were used for elaborating the B-ring core structure of 24. [51][52][53] On the other hand, only small quantities of the final compound could be obtained in most cases because the many reaction steps were needed for the total synthesis.…”
Section: Cortistatins From the Marine Spongementioning
confidence: 99%
“…In this one-pot three-step process, an internal hydroxyl group acted as nucleophile (Scheme 32). 112 This strategy has previously been employed in synthetic efforts towards the cortistatin family 28,275 (cf. Scheme 69 for another example).…”
Section: Scheme 31mentioning
confidence: 99%